The role of multislice computed tomography of the chest in patient with COVID 19 pneumonia - Sanjit Kumar Sah; Mona Ahmed Fouad Hafez; Sally Fouad Kamel Tadros; Yasmine Hamdy Elhinnawy (Cairo : Sanjit Kumar Sah, 2020)
Corona virus disease 2019 (COVID-19) is a highly infectious disease that causes severe respiratory syndrome that was first discovered by end of 2019 in Wuhan, China and spread globally. On 11 March 2020, the World Health Organization has declared the pandemic of COVID-19. Corona virus disease 2019 is caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) formerly known as 2019 novel corona virus (2019-nCo V).The average incubation period of SARS-CoV-2 infection is 4-5 days, the maximum being 14 days. The clinical findings are variable ranges from flu like symptoms to severe respiratory distress syndrome.Multidetector computed tomography is the most sensitive imaging technique for the diagnosis of COVID-19, showing different lung alterations such as GGO, consolidations, crazy paving, vascular dilatation, parenchymal bands and architectural distortion; regarding disease course several radiological patterns are observed. Multidetector computed tomography of the chest is a valid imaging method for assessing the extent and severity of COVID-19 pneumonia and can be used as a standard method in early management of patients
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Radio-Diagnosis
Issued also as CD
Keywords: COVID-19 pneumonia; Multidetector CT; Multislice computed tomography